2005
DOI: 10.1007/s10350-004-0861-z
|View full text |Cite
|
Sign up to set email alerts
|

Stapled Hemorrhoidopexy vs. Diathermy Excision for Fourth-Degree Hemorrhoids: A Randomized, Clinical Trial and Review of the Literature

Abstract: Stapled hemorrhoidopexy was not effective as a definitive cure for the symptoms of prolapse and itching in patients with fourth-degree hemorrhoids. Moreover, stapled hemorrhoidopexy induced the appearance of a new symptom, tenesmus, in 40 percent of the patients. Therefore conventional diathermy hemorrhoidectomy should continue to be recommended in patients with symptomatic, prolapsed, irreducible piles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
164
3
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(175 citation statements)
references
References 22 publications
2
164
3
6
Order By: Relevance
“…In group A, 11 patients were having satisfactory outcome and in group B, 8 patients were have satisfactory outcome. When results of two groups were compared for postoperative pain it shows significant statistical difference in between two groups like those of the other controlled studies conducted by Ortiz H et al 18 and Rowsell M et al 19 reported in the literature, 20 the results reported here show that stapled hemorrhoidectomy is associated with significantly less postoperative discomfort than conventional hemorrhoidectomy.…”
Section: Resultssupporting
confidence: 75%
“…In group A, 11 patients were having satisfactory outcome and in group B, 8 patients were have satisfactory outcome. When results of two groups were compared for postoperative pain it shows significant statistical difference in between two groups like those of the other controlled studies conducted by Ortiz H et al 18 and Rowsell M et al 19 reported in the literature, 20 the results reported here show that stapled hemorrhoidectomy is associated with significantly less postoperative discomfort than conventional hemorrhoidectomy.…”
Section: Resultssupporting
confidence: 75%
“…8,23 Tenesmus was more commonly reported in stapled hemorrhoidopexy and authors have attributed this to the presence of a low rectal suture. 21 Intramural fistulization was reported in 0.02% of cases, all on the staple line, and required clearance and elastic drainage for management. 23 Submucosal anastomotic cysts were reported postoperatively and these were associated with the retention of fecolith material at the anastomotic level.…”
Section: Discussionmentioning
confidence: 99%
“…3,[17][18][19][20] Early thrombosed external hemorrhoids (TEH) were also reported, with the overall early occurrence rate ranging from 0 to 13% and a median occurrence of 4.51%. 21 Overall rates of urinary retention ranged from 0 to 22%. 6 Few articles documented whether or not urinary catheterization was required to treat the retention.…”
Section: -16 Documented Complications Of Hemorrhoidopexy Porrettmentioning
confidence: 99%
See 2 more Smart Citations